فاعمية برنامج كمبيوتر متعدد الوسائط قائم عمى الرجع التكيفي بتقنية الذكاء الاصطناعي عمى اتقان التعمم وبقاء أثره لدي طالبات كمية التربية بجامعة الامير سطام. - ىالو خيري الجوىر (Journal of Babylon Center for Humanities Studies, 2022)
The first and second students in the College of Education in Al-Dilam were selected in a cluster-intentional manner in the first semester of the academic year 2021/2022. The researcher calculated the standard deviation, the arithmetic mean, and the value of (t) to show the significance of the differences between the mean scores of the students of the experimental and control groups in the post application of the achievement test, The researcher refers to the use of adaptive feedback using artificial intelligence technology through multi-media computer programs with artificial intelligence technology,(Blackboard) provides the students with the opportunity to repeat, practice, see and read several times according to their abilities, thus providing an opportunity for the students to practice and repetition, in addition to the forms and fees provided by the program that lead to the development, improvement and mastery of learning outcomes and the survival of its impact,The results of the study concluded that a multimedia computer program with adaptive feedback based on artificial intelligence technology gives an ability to learn (90%) in dimensional cognitive achievement. 90%) in favor of adaptive regression in posterior achievement, the researcher recommended the use of many multimedia computer programs based on artificial intelligence technology in teaching computer courses and other courses within the faculties of education.